An Empirical Analysis of Money, Exchange Rate and Inflation Dynamics in Sudan - Yol, Marial Awou (2001)
The issue of the direction of dynamic causality among macroeconomic variables has been a divisive issue among the economists. It is argued that an exogenous expansion in money supply leads to a long-run cumulative causation among macroeconomic variables. Domestic monetary expansion causes domestic interest rates to fall, initiating an incipient capital outflows and a subsequent depreciation of domestic currency. This process, in tum, raises domestic prices via the prices of imported goods, which results in subsequent fall of domestic real money balances and wages. Maintaining such an-accommodative monetary policy can doubtlessly give rise to exchange rate-inflation spiral that can generate and sustain a vicious dynamic process --of -rising prices '-and depreciating exchange rate which can plague the economy for a long time. The main objective of this study is to examine and analyze the nature of the causality among money, exchange rate, nominal wages, domestic inflation and real output in the context of the Sudanese economy from 1970 to 1999. The study attempts to determine the direction of causality among the variables and suggest appropriate policy actions that the concerned authorities might employ to break this vicious dynamic causality in order to stabilize the performance of the Sudanese economy. To achieve this, the study employs the cointegration techniques and vector error-correction model (VECM) to analyze this dynamic causal relationships using annual data on money supply, exchange rate, nominal wages, consumer price index, and real output. While the Johansen cointegration tests indicate two cointegrating equations (exchange rate and money), the Granger-causality tests indicate that inflation, nominal wages and inflation are weakly exogenous variables. The empirical results indicate that, in the short run, a rise in consumer price index (inflation) and money supply cause the exchange rate to depreciate, while a rise in nominal wages and real output cause the exchange rate to appreciate. However, in the long run, while a rise in consumer price index and real output causes the exchange rate to appreciate, a rise in money supply results in exchange rate depreciation. In addition, a rise in exchange rates (depreciation) and consumer price index in the short run causes money supply to rise while a rise in nominal wages reduces it. However, in the long run, a rise in domestic prices, exchange rate (depreciation) and real output cause money supply to rise.